Ukraine’s food security under martial law - Pilshchikov, Illia; Duzhyk, Nataliia (My University, 2023)
An assessment of Ukraine’s current food security and a forecast of forthcoming trends are carried out. A number of measures aimed at improving the country’s food security are considered. Particularly, it is necessary to rethink the logistics of agricultural supply, to modernize Ukraine’s agricultural production with the help of international grants and credits, and to reform the market mechanisms by ensuring their transparency. Здійснено оцінку поточного стану продовольчої безпеки України та прогноз майбутніх тенденцій. Розглянуто низку заходів, спрямованих на покращення продовольчої безпеки країни. Зокрема, необхідно переосмислити логістику постачання сільськогосподарської продукції, модернізувати сільськогосподарське виробництво України за рахунок міжнародних грантів і кредитів, реформувати ринкові механізми, забезпечивши їх прозорість.
Keywords: кафедра ділової іноземної мови та міжнародної комунікації; agricultural production; economic growth; food security index; state legislation; сільськогосподарське виробництво; економічне зростання; індекс продовольчої безпеки; державне регулювання